THE INFLUENCE OF THE VIDEO CRITIC METHOD ON THE UNDERSTANDING OF MORALS OF CLASS IX STUDENTS OF MTS AL-ITTIHADIYAH PANGKALAN MANSYUR - Nurul Aini; Khairuddin Lubis; Yurmaini Yurmaini; Khairul Anwar (Edusoshum : Journal of Islamic Education and Social Humanities, 2023)
This research aims to determine the effect of the video criticism method on understanding morals in class IX MTs students. The type of research carried out was quantitative with an experimental method using a One Group Pretest and Post Test Design research design. The population in this study were all IX students of MTs Al Ittihadiyah Pangkalan Mansyur, with a sample selected using the Non Probability Sampling technique, namely class IX Ali, totaling 29 people. The data collection techniques used were pretest and posttest. The results of research using the IBM SPSS (Statistical Product and Service Solution) v.25 data processing program show that the average (mean) post test score was 76.38, while the average (mean) pretest score was 44.14. With the highest pretest score of 55 and post test of 90, the difference in score obtained is 35 (90-55). This shows that the video criticism method is able to improve students' moral understanding very well. Based on the mean difference test with Paired Sample T-test analysis on IBM SPSS Statistics v.25, the sign value (2-tailed) = 0.00 was obtained which was compared with the calculated result of sign a = 0.05 with a confidence level of 95%. From the results of these calculations, the sign is 0.00 ≤ 0.05, which means that H_0 is rejected or H_1 is accepted. Thus, the average student post test score is higher than the average student pretest score.